Too risky, too large, too late, or too mild—Reasons for not treating ischemic stroke patients and the related outcomes - Behrndtz, Anne Brink; Damsbo, Andreas Gammelgaard; Blauenfeldt, Rolf Ankerlund; Andersen, Grethe; Speiser, Lasse Ole; Simonsen, Claus Ziegler (Frontiers in Neurology, 2022)
Background: Despite effective treatments, many patients are still not offered reperfusion therapy for acute ischemic stroke. Methods: We present a single center observational study on acute ischemic stroke patients, presenting as candidates for reperfusion therapy but deemed ineligible after work-up. Reasons for not treating was obtained by studying patient files and subsequently grouped in “too risky” (e.g. anticoagulant use, comorbidities), “too large” (large infarct), “too late” (late presentation of stroke and wake-up strokes) or “too mild” (clinically mild/remitting symptoms). Modified Rankin scale (mRS) score was prospectively collected in all patients by a structured telephone interview. All non-treated patients with National Institute of Health Stroke Scale (NIHSS) score of 0-5 were compared with a similar cohort that was treated. Results: Of 529 patients with acute ischemic stroke arriving as reperfusion therapy candidates, 198 (37.4%) were not treated. The majority (42%) was not treated due to admission outside the treatment window (too late) and 24% had absolute contraindications (too risky). Only 8% was excluded because their infarct was too large (median Alberta Stroke Program Early CT score 3 [2-4]). In the group “too mild” (14%) the percentage of patients not being independent at 90 days was 30%. Adjusted odds ratio for a better outcome (lower mRS) among treated patients with NIHSS 0-5 compared with non-treated was 1.93 (95% confidence interval 1.15-3.23). Conclusions: Presenting outside the treatment window is still the most common reason for not receiving therapy. Our study suggests benefit of thrombolysis for patients with mild symptoms.